2014
DOI: 10.1159/000363236
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Distance between Small Intramural Uterine Fibroids and the Endometrium on the Pregnancy Outcomes of in Vitro Fertilization-Embryo Transfer

Abstract: Aim: To explore the effects of the distance between small intramural uterine fibroids (≤4 cm) and the endometrium on the outcomes of in vitro fertilization-embryo transfer (IVF-ET). Methods: We prospectively analyzed pregnancy outcomes in 117 infertile women with small intramural uterine fibroids and 117 infertile women without uterine fibroids who all underwent IVF-ET. The size and number of small intramural uterine fibroids and the shortest distance between the small intramural uterine fibroids and the endom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Especially, 23 of these studies have controlled the potential confounding factors by matching the age, number of embryos, number of cycles, and/or other factors between the study and the control groups. 5 other studies randomly had women enrolled into the control group from the same population without factors matched [ 28 , 30 , 32 , 44 , 51 ], but in the studies of Lu and Long, the age and some other important factors had no statistical difference between the study and control groups [ 28 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially, 23 of these studies have controlled the potential confounding factors by matching the age, number of embryos, number of cycles, and/or other factors between the study and the control groups. 5 other studies randomly had women enrolled into the control group from the same population without factors matched [ 28 , 30 , 32 , 44 , 51 ], but in the studies of Lu and Long, the age and some other important factors had no statistical difference between the study and control groups [ 28 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…The deficiency of this meta-analysis is mainly due to the heterogeneity among the included studies. Firstly, 7 of the 28 studies were prospective [ 30 , 35 , 39 , 42 , 43 , 46 , 48 ], but the others were retrospective in design. Secondly, 10 of the 28 studies recorded a woman once because they only enrolled the first cycle of a woman undergoing IVF treatment [ 29 , 34 , 37 , 39 , 40 , 45 , 47 , 48 , 50 , 53 ], but the others may have recorded a woman more than one time because they enrolled every cycle of the previous IVF treatments.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29][30][31] In contrast, there are studies that demonstrate an unfavorable effect on IVF pregnancy rates in women with fibroids that do not appear to encroach the endometrial cavity. 26,[32][33][34][35][36][37] In one study, nonencroaching fibroids decreased the chances of ongoing pregnancy after IVF by half. 37 Another study revealed that implantation rates after IVF were 4.3% in women with submucosal fibroids and 6.4% in women with intramural fibroids, in comparison to 15.7% in women without fibroids.…”
Section: How Do Uterine Fibroids Cause Infertility?mentioning
confidence: 99%
“…Inclusion criteria were as follows: patients had severe IUA confirmed by the diagnosis of hysteroscopy according to the American Fertility Society in 1988, and their clinical manifestations included amenorrhea, decrease in menstrual flow, infertility and repeated miscarriage [15,16]. Exclusion criteria were as follows: patients had a history of irregular menstrual cycle or abnormal uterine bleeding, abnormal sex hormone levels, sex hormone therapy, cardiovascular, liver and thrombotic diseases and ovarian tumors as well as intrauterine diseases such as endometrial polyps and submucosal uterine fibroids.…”
Section: Methodsmentioning
confidence: 99%